Does Native Script Exposure Influence Second Language Early Literacy Skills?: A Preliminary Study in South Indian Preschoolers - Mohan, Megha; Francis, Tinu R.; Bhat, Jayashree S. (Journal of Child Science, 2022)
The preschool period is marked by the development of several domains such as communication, cognition, social skills, and literacy skills. As language and literacy skills overlap during the preschool period, it is important to understand the dynamics of language and literacy in early school years. Due to language diversity, India does not bear a single-language system, and often the language spoken at home may not be the same at school for curricular instructions. Therefore, the present study focuses on the influence of script in bi- or multilingual scenarios in India. More importantly, the home language may or may not have its specific script; thus, facilitating early literacy skills at home can be questionable. The study followed a cross-sectional study design. One hundred and forty participants were divided into two groups based on their native language (Malayalam and Tulu groups). Each group was further divided based on their age, younger and older groups. An early literacy checklist and a parent perception questionnaire were developed to assess the early literacy skills in second language (L2). The findings revealed a developmental trend in early literacy skills in children with the older group performing better than the younger group. The study results also shed light on this less researched domain of influence of native script on L2 learning in a linguistically diverse country like India. The study's findings emphasize the parental understanding of the importance of home literacy–based activities for children and evaluation of early literacy skills which will help in early identification and treatment.
Keywords: early literacy skills; preschoolers; script; L2 learning; bilinguals; home literacy